FIM Business Center - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
FIM Business Center was inaugurated on 16th March 2016, with the following objectives...